(untitled) (LEGAL DIALOGICA, 2025)
This study aims to determine the law enforcement against criminal acts of sexual harassment and to determine the factors that influence law enforcement against criminal acts of sexual harassment in Maros Regency. The research method used is empirical legal research. Data is obtained through interviews with law enforcement officials, victims, the community and document studies. The results of this study indicate that Law Enforcement against Criminal Acts of Sexual Harassment that occurred in Maros Regency (Case Study at the Maros Resort Police) has not been effective, this is because the criminal acts of sexual harassment that occurred from 2021 to 2024 have not decreased significantly and the number is still relatively high. Furthermore, the factors that influence are law, law enforcement officials, facilities, society, and culture. It is hoped that families and communities, especially parents, will better supervise the association of children in order to prevent criminal acts of sexual harassment, victims have the courage to report incidents of sexual harassment that happen to them, in order to avoid repetition of similar acts in the future, the Maros Resort Police can conduct socialization to schools to prevent criminal acts of sexual harassment against minors, and the government can make policies for legal protection for women and children who are victims of sexual harassment. Abstrak: Penelitian ini bertujuan untuk mengetahui penegakan hukum terhadap tindak pidana pelecehan seksual serta mengetahui faktor-faktor yang memengaruhi penegakan hukum terhadap tindak pidana pelecehan seksual di Kabupaten Maros. Metode penelitian yang digunakan yaitu penelitian hukum empiris. Data diperoleh melalui wawancara dengan aparat penegak hukum, korban, masyarakat dan studi dokumen. Hasil penelitian ini menunjukkan Penegakan Hukum terhadap Tindak Pidana Pelecehan Seksual yang terjadi di Kabupaten Maros (Studi Kasus di Kepolisian Resor Maros) belum efektif, hal ini disebabkan tindak pidana pelecehan seksual yang terjadi dari Tahun 2021 hingga 2024 belum mengalami penurunan yang berarti dan jumlahnya masih tergolong tinggi. Lebih lanjut faktor-faktor yang memengaruhi yaitu hukum, aparat penegak hukum, sarana dan fasilitas, Masyarakat, serta budaya. Diharapkan agar keluarga dan masyarakat khususnya orang tua lebih mengawasi pergaulan dari anak-anak agar mencegah terjadinya tindak pidana pelecehan seksual, korban memiliki keberanian untuk melaporkan kejadian pelecehan seksual yang menimpa dirinya, agar menghindari terjadinya pengulangan perbuatan serupa di kemudian hari, Kepolisian Resor Maros dapat melakukan sosialisasi ke sekolah-sekolah guna mencegah terjadinya tindak pidana pelecehan seksual terhadap anak dibawah umur, serta pemerintah dapat membuat kebijakan terhadap perlindungan hukum kepada korban perempuan dan anak yang menjadi korban pelecehan seksual.